AI in Pharmaceutical Manufacturing: Present Senario in Pharma Industry - Kumar, Kotha Kranthi; Jyothi M. (Pharmaceutical Research - Recent Advances and Trends Vol. 1, 2024)
Artificial intelligence (AI) is becoming a potential model that uses human knowledge to solve difficult problems more quickly. The field of drug discovery, pharmaceutical formulation, and dosage form testing is about to undergo a radical change because of remarkable developments in AI and machine learning. Researchers may find disease-associated targets and anticipate how they would interact with possible treatment options by using AI-developed programs that examine vast biological data like proteomics and genomics. This raises the likelihood of successful pharmaceutical approvals by allowing for an efficientive and concentrated approach to drug development. AI may also save development costs by streamlining the research and development process. AI models enable pharmaceutical companies to design, automate, evaluate, and monitor human-centric and integration-centric activities and processes, helping them to deliver novel medicines more cost-effectively and on time. It improves repeatability, control, and visibility inside the firm while also streamlining and simplifying operations. It may help pharmaceutical manufacturers quickly understand and implement procedures and systems to improve their company operations, offering them the agility they require to respond to changing situations, new legislation, and expectations for a short product delivery life-cycle. Artificial intelligence evaluates patient information and enables the personalization of medicine approaches, hence improving patient adherence and treatment outcomes. This thorough overview section delves into the many uses of AI in the creation of drug delivery, formulation development, process optimization, evaluation, and PK/PD studies. The article discusses the benefits and drawbacks of several AI model strategies applying in pharmaceutical manufacturing. However, the pharmaceutical industry's increasing research and investment in AI creates several prospects for enhancing the treatment of patients and drug development processes.